Left Prefrontal Activity Reflects the Ability of Vicarious Fear Learning: A Functional Near-Infrared Spectroscopy Study - Qingguo Ma; Yujing Huang; Lei Wang (The Scientific World Journal)
Fear could be acquired indirectly via social observation. However, it remains unclear which cortical substrate activities are involved in vicarious fear transmission. The present study was to examine empathy-related processes during fear learning by-proxy and to examine the activation of prefrontal cortex by using functional near-infrared spectroscopy. We simultaneously measured participants’ hemodynamic responses and skin conductance responses when they were exposed to a movie. In this movie, a demonstrator (i.e., another human being) was receiving a classical fear conditioning. A neutral colored square paired with shocks (CSshock) and another colored square paired with no shocks (CSno-shock) were randomly presented in front of the demonstrator. Results showed that increased concentration of oxygenated hemoglobin in left prefrontal cortex was observed when participants watched a demonstrator seeing CSshock compared with that exposed to CSno-shock. In addition, enhanced skin conductance responses showing a demonstrator's aversive experience during learning object-fear association were observed. The present study suggests that left prefrontal cortex, which may reflect speculation of others’ mental state, is associated with social fear transmission.